(untitled) (Interdisciplinary Studies Journal, 2024)
The organization of this text aims to present analyses of the discourses promoted by legal determinations directed at Brazilian High School, based on the key concept of "hegemony." It starts from the premise that the endeavor of unveiling curricular discourses to point out marks of the hegemonic process involves some elements, namely: the State playing a role as an educator, building pedagogical relationships through a set of curricular documents, and committing acts of symbolic violence, which we consider an expression of its hegemonic power, that is, defining what is considered valid (policies, programs, competencies, knowledge, among others). To develop the analyses, curricular texts/documents (CTD) published between 2009 and 2019 are used as source and object, including the National Curriculum Guidelines for High School (DCNEM) of 2012, Law 13.415, known as the High School Reform, of 2017, and the National Common Curricular Base for High School, of 2018. Each discursive justification develops according to the interests of the historical moment, and every choice derives from arbitrations that prioritize certain aspects over others equally relevant (VALLE, 2014).